Ultrasound‐Guided Nerve Blocks in Emergency Medicine Practice. (1st March 2016) - Amini, Richard; Kartchner, Jeffrey Z.; Nagdev, Arun; Adhikari, Srikar
Abstract : Objectives: The purpose of this study was to investigate the current practice of ultrasound (US)‐guided regional anesthesia at academic emergency departments, including education, protocols, policies, and quality assessment. Methods: We conducted a cross‐sectional study. A questionnaire on US‐guided nerve blocks was electronically sent to all emergency US directors and emergency US fellowship directors. Results: A total of 121 of 171 academic institutions with an emergency medicine residency program participated in this study, representing a 71% response rate. Eighty‐four percent (95% confidence interval [CI], 77%–91%) of programs perform US‐guided nerve blocks at their institutions. The most common type of nerve block performed is a forearm nerve block (ulnar, median, or radial). The most common indication for US‐guided nerve blocks is fracture pain management. Only 7% (95% CI, 2%–12%) of programs have a separate credentialing pathway for US‐guided nerve blocks. Regarding quality assessment review of US‐guided nerve blocks, none of the programs have a separate program in place. In 57% (95% CI, 48%–66%) of programs, it is a component of the emergency US quality assessment program. Eighty‐four percent (95% CI, 77%–90%) of programs do not have specific agreements with other specialty services with regard to performing US‐guided nerve blocks in the emergency department. The most common educational methods used to teach US‐guided nerve blocks are didactic sessions, at 67% (95% CI, 59%–75%); online resources, at 54% (95% CI, 45%–63%); and supervised training with real patients, at 48% (95% CI, 39%–57%). Conclusions: Ultrasound‐guided nerve blocks are performed at most academic emergency departments. However, there is a substantial variation in the practices and policies within these institutions.